2007
DOI: 10.1590/s0103-84782007000500032
|View full text |Cite
|
Sign up to set email alerts
|

Dietas para frangos de corte contendo quirera de arroz

Abstract: RESUMO O experimento foi realizado para avaliar o uso da quirera de arroz na dieta de frangos de corte. Foram utilizados INTRODUÇÃOO avanço da nutrição exige cada vez mais dos nutricionistas a busca por alimentos com alta digestibilidade que sejam economicamente viáveis. A avaliação de alimentos alternativos e o uso destes na alimentação animal possibilitam a redução dos custos de produção, com reflexos diretos sobre a viabilidade do sistema produtivo avícola.O arroz (Oryza sativa L.) é mundialmente produzido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…The carcass yield results of quails are consistent with those reported for broilers (Brum Júnior et al, 2007), where no influence of corn substitution by broken rice at levels of 0, 20, or 40% in the diet on broiler carcass or cuts yields was observed. Cancherini et al (2008) also did not find any significant effects of dietary broken rice inclusion on broiler carcass yield.…”
Section: Corn Replacement By Broken Rice In Meat-type Quail Dietssupporting
confidence: 87%
See 2 more Smart Citations
“…The carcass yield results of quails are consistent with those reported for broilers (Brum Júnior et al, 2007), where no influence of corn substitution by broken rice at levels of 0, 20, or 40% in the diet on broiler carcass or cuts yields was observed. Cancherini et al (2008) also did not find any significant effects of dietary broken rice inclusion on broiler carcass yield.…”
Section: Corn Replacement By Broken Rice In Meat-type Quail Dietssupporting
confidence: 87%
“…However, in the present study, increasing soybean oil inclusion levels as broken rice inclusion increased did not have the same effect. Although no effect on gizzard yield was observed, Brum Júnior et al (2007) and Nanto et al (2012) found reduced gizzard weight as the substitution of corn by broken rice and dehulled paddy rice increased. The authors associated this result to the reduced stimulation of this organ as a consequence of the higher starch and lower non-starch polysaccharide levels of broken rice (Choct, 2002).…”
Section: Corn Replacement By Broken Rice In Meat-type Quail Dietsmentioning
confidence: 91%
See 1 more Smart Citation
“…A avaliação de alimentos alternativos e seu uso na alimentação animal possibilitam a redução dos custos de produção e têm reflexos diretos na viabilidade do sistema produtivo avícola (Brum Jr. et al, 2007). Do ponto de vista financeiro, a ração participa com 70% do custo total e este custo é variável em função do preço do farelo de soja e do milho, componentes com parcelas significativas na composição da ração do frango.…”
Section: Introductionunclassified
“…Moreover, price variation of these ingredients throughout the year creates an opportunity for the use of alternative ingredients in animal feed. Alternative food may maintain production rates and quality of the final product, in addition to reducing the production costs, becoming useful in profit optimization (Brum Júnior et al, 2007).…”
Section: Introductionmentioning
confidence: 99%